Effects of ω-3 Polyunsaturated Fatty Acids on Coronary Atherosclerosis and Inflammation: A Systematic Review and Meta-Analysis - Gao, Zheng; Zhang, Dewen; Yan, Xiaocan; Shi, Hekai; Xian, Xiaohui (Frontiers in Cardiovascular Medicine, 2022)
Background and Purpose Multiple guidelines suggest the ω-3 polyunsaturated fatty acids (ω-3 PUFAs) help to prevent major vascular events of coronary heart disease (CHD), but the data on large trials of ω-3 fatty acids are controversial. We reviewed the available evidence to determine the effect of ω-3 PUFAs on coronary atherosclerosis. Materials and Methods Literature were from online databases. Randomized controlled trials (RCTs) or observational studies were acceptable. Quantitative data synthesis was conducted using R version 4.1.2. Each outcome was calculated using standardized mean difference (SMD) in a random-effect model. Sensitivity analysis was conducted for each outcome. A total of 21 RCTs and 1 observational study with 2,277 participants were included. Results Meta-analysis indicated a benefit of ω-3 PUFAs on coronary atherosclerosis, namely, (1) ω-3 PUFAs can reduce the atherosclerotic plaque volume (SMD −0.18; 95% CI −0.31 to −0.05); (2) ω-3 PUFAs can help reduce the loss of the diameter of the narrowest segments of coronary arteries in patients with CHD (SMD 0.29; 95% CI, 0.05–0.53); (3) ω-3 PUFAs do not have significant effect on volume of lipid plaque in coronary arteries (SMD −1.18; 95% CI −2.95 to 0.58), volume of fiber plaque (SMD 0.26; 95% CI −0.81 to 1.33), and calcified plaque (SMD 0.17; 95% CI −0.55 to 0.89); and (4) ω-3 PUFAs had no significant effect on endothelial inflammatory factors in peripheral blood. Conclusions We confirmed that ω-3 PUFAs benefit patients with CHD by reducing the progression of coronary atherosclerosis. We indicated that the benefits were not caused by reducing endothelial inflammations of coronary arteries. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021285139, identifier: CRD42021285139.